Women as Transformative Agents of Agricultural and Rural Development - Ávila Garavito, Diana Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This case study examines the participation of women affected by the armed conflict in productive initiatives in the departments of Nariño, Cauca, and Valle del Cauca. Under the direction of the NGO Alliance for Solidarity, the study covers experiences in urban and rural areas, highlighting the importance of rural women who face different types of violence and forced displacement. Various productive experiences were systematized, from community gardens to food processing, and a timeline was reconstructed that reflects the victimizing events, the arrival of institutions and NGOs, and the development of legally constituted productive initiatives in 2017. The reconstruction of the experience is framed within the '7 Capitals of the Community,' addressing human, social, cultural, political, natural, financial-productive, and infrastructural aspects. An empowerment survey evaluated five spheres, showing an increase in empowerment in Afro-descendant communities in Nariño (from 62.9% to 78.7%), mestizo women in Tambo, Cauca (from 46.4% to 97.8%), and indigenous women in Valle del Cauca (from 50% to 80%). Productive initiatives and gender training are essential for empowerment as they contribute to the reconstruction of the social fabric and rural development. Successful experiences have a positive impact on local processes.